APPLYING BILINGUAL TO ENHANCE GRAMMAR LEARNING FOR SPEAKING: SYSTEMATIC LITERATURE REVIEW - Cahyani, Fibria; Suseno, Edy (Innovare Journal of Social Sciences, 2023)
For concepts to be communicated, sentences must be constructed properly. To achieve these goals, it is essential to keep the ability to modify grammatical rules. A review of ten credible research revealed that many students in Asia and Europe have grammar difficulties. The age range of these students is 6–24. Information was found on the Google Scholar website. All articles were published between 2019 and 2022. The writings’ themes center on improving grammar, speaking, and bilingual skills. The gathered data were analyzed using a systematic literature review method. Analyzing such data, it is found that all of the authors used bilingual instruction to teach the participants grammar in the English class. Implementing such a strategy leads to improvements in the pupils’ speaking abilities. The development of other abilities such as reading, writing, and listening is impacted. This discovery will help teachers teach related subjects. It also motivates other researchers to come up with new findings.